Perspectives and provocations in early childhood education - Vasquez, Vivian Maria; Wood, Jeffrey W. (Early childhood education assembly., 2012)
Mandates to implement practices that are antithetical to what we embrace as supportive of young children's literacy learning are pervasive. Teachers of young children are asked to teach-to-the test in ways that take away opportunities for holistic, thoughtful, play-oriented practices that allow children to construct knowledge through contextualized and purposeful experiences. In 2009 the Early Childhood Assembly was formed by a group of early childhood educators to provide a home at the National Council for Teacher of English for all who work with young children. Perspectives and Provocations in Early Childhood Education is a publication of the ECEA. The publication is intended to support teachers of young children and those interested in studying about early literacy by putting on offer texts with a strong emphasis on promoting thoughtful practices that enhance the teaching and learning of young children within and across diverse communities. All royalties from the book go to the ECEA to help the organization advance its goals of providing scholarships for early childhood teachers to participate in conferences and professional development events.